Adaptasi Setek Batang Tanaman Lada (Piper nigrum L.) Menggunakan Komposisi Media Gambut dan Pupuk Organik Kotoran Kambing yang Berbeda - Aminuddin, Muhammad; Saputra, Riza Adrianoor; Sofyan, Antar (Jurnal Agro Industri Perkebunan, 2022)
Peatlands have good prospects for use as agricultural land. Peatlands have many problems, one of which is high acidity. Organic goat manure is expected to be able to overcome the problem of peatlands. Therefore, this study aimed to determine the best combination of peat media and organic goat manure on the pH of the media and the growth of pepper plant stem cuttings. This research was carried out for three months (October to December 2021), including taking peat soil in Sukamaju Village, Landasan Ulin Timur District, Banjarbaru, South Kalimantan; taking pepper cuttings in Senakin Village, Kotabaru Regency, South Kalimantan; planting pepper cuttings in the Greenhouse Department of Agroecotechnology Faculty Agriculture at Lambung Mangkurat University, Banjarbaru, South Kalimantan; and observing the pH of cutting media at the Production Laboratory of the Agroecotechnology Department, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan. This research used a completely randomized design (CRD) with one factor. The factor studied was the composition of the planting medium (K), which consisted of five treatments: k1 = 100% peat + 0% organic goat manure, k2 = 75% peat + 25% organic goat manure, k3 = 50% peat + 50% organic goat manure, k4 = 25% peat + 75% goat manure organic fertilizer, and k5 = 0% peat + 100% goat manure organic fertilizer. The results showed that the treatment with the composition of 0% peat + 100% organic goat manure (k5) is the best for increasing the pH of the media (6.50). The composition of 50% peat + 50% organic goat manure (k3) was the best in increasing shoot height and number of leaves (4.44 cm shoot height and 1.08 leaves), but not different from the composition of 25% peat + 75% organic fertilizer goat manure (k4) on the percentage of live cuttings, number of shoots, and leaf width (70% live cuttings, 0.70 shoots, and 2.69 cm leaf width).